A study of distilled water and zamzam water as dielecric dense patch antenna at 5 GHz - N. H. Moktar; W. I. Roseli; M. T. Ali; R. A. Awang (Institute of Advanced Engineering and Science, 2019)
This paper was performed in order to study about distilled water and zamzam water which act as dielectric dense (DD) patch antenna at 5 Ghz applications. This antenna is proposed and designed using FR-4 substrate that sandwiched together to perform DD structure. The proposed antennas employ simple rectangular structure that fed with inset feeder surround by electromagnetic bandgap (EBG) structure.In order too enhance the gain, superstrate is applied on top of the antenna. This antenna offers a wideband return loss of more than -10dB between 4.41-5.52Ghz (around 22.2%) which can be applied in 5 Ghz applications. Details of DD water antenna of center frequency for 5 Ghz is presented and discussed.